Permeability measurements using rate-transient analysis (RTA): Comparison with different experimental approaches. (15th January 2022) - Shabani, Mohammadebrahim; Ghanizadeh, Amin; Clarkson, Christopher R.
Highlights: The RTA and PTA methods were used to extract permeability values from measurements performed on a tight siltstone core plug sample. The slope of the square root time plot and the time at the end of linear flow were used to derive two independent permeability and pore volume values. The pore volume and permeability estimate from the production data are in good agreement with the results from conventional experimental approaches. The RTAPK method closely represents the conditions under which wells produce in the field, and the data are analyzed similarly. Abstract: Reservoir engineers commonly apply rate-transient analysis (RTA) and pressure-transient analysis (PTA) methods to analyze multi-fracture horizontal wells (MFHWs) completed in unconventional reservoirs quantitatively for reservoir and hydraulic fracture properties. Data from core analysis techniques are commonly used to provide important input for RTA-PTA models. However, conventional laboratory techniques (i.e., steady-state and non-steady-state fluid flow) do not reproduce the operating conditions that MFHWs are subjected to in the field. In the current work, laboratory techniques that better reproduce these boundary conditions are explored and compared to more traditional core analysis methods. For this study, RTA methods are applied to gas produced from core plugs and PTA methods are applied to gas injection-fall-off data at the start of the core test before gas production. While the RTA method has been previously described by the authors, the application of the PTA method to provide an early, and fast, estimate of permeability is unique to this study. Further, our previous experimental setup for performing RTA was modified to accommodate not only the use of both RTA/PTA methods, but also the use of conventional core analysis methods (steady-state and non-steady-state methods) to allow for direct comparison of all methods. For both RTA and PTA core tests, the observed flow-regime sequence is transient linear flow followed by boundary-dominated flow, which is the same sequence that is commonly observed in the field for MFHWs producing from low-permeability and shale reservoirs. Two independent permeability values were estimated using the slope of the square root time plot and the time at the end of linear flow for each test. The pore volume of the samples were also estimated using the RTA method. Permeability and pore volume values obtained from the RTA method, referred to as 'RTAPK' previously, were in good agreement with those obtained from more conventional core testing methods (average coefficient of variation = 8%). The derived permeabilities from the time at the end of linear flow during the fall-off test were close to other permeabilities. In contrast, the square root time plot (fall-off) resulted in significantly higher permeabilities attributed to the experimental artifact caused by substantial dead volume in the injection port. The primary advantage of the RTA core analysis method is the accelerated test-time. For samples with permeability values ranging between 0.1 and 3 mD, the apparent gas permeabilities can be estimated in less than 3 to 10 minutes using both fall-off and production data.